Discovery of novel dual inhibitors of receptor tyrosine kinases EGFR and IGF-1R. (1st January 2017) - Hempel, Cornelius; Totzke, Frank; Schächtele, Christoph; Najjar, Abdulkarim; Sippl, Wolfgang; Ritter, Christoph; Hilgeroth, Andreas
Abstract: Novel 4-benzylamino benzo-anellated pyrrolo[2, 3- b ]pyridines have been synthesized with varied substitution patterns both at the molecular scaffold of the benzo-anellated ring and at the 4-benzylamino residue. With a structural similarity to substituted thieno[2, 3- d ]pyrimidines as epidermal growth factor receptor (EGFR) inhibitors, we characterized the inhibition of EGFR for our novel compounds. As receptor heterodimerization gained certain interest as mechanism of cancer cells to become resistant against novel protein kinase inhibitors, we additionally measured the inhibition of insulin-like growth factor receptor IGF-1R which is a prominent receptor for such heterodimerizations with EGFR. Structure–activity relationships are discussed for both kinase inhibitions depending on the varied substitution patterns. We discovered novel dual inhibitors of both receptor tyrosine kinases with interest for further studies to reduce inhibitor resistance developments in cancer treatment.